PERANCANGAN MOTION GRAPHIC VIDEO ANIMASI SEBAGAI SARANA IKLAN PROMOSI DAN INFORMASI - Idris, Iswandi; Pangaribuan, Hose Ronaldo; Khair, Rizaldy (ITScience (Information Technology and Science), 2022)
Advertising is a way to promote a product, brand or service to an audience to drive interest, engagement and sales. Social media can be utilized as a medium for spreading motion graphic content more widely and efficiently. This animation research aims to provide information on the effect of designing animation videos as a means of promotional advertising on Ucok Sticker and produce product advertising videos that can increase consumer appeal. From the research conducted obtained the results in the form of a 2D video animation product advertisements used as a promotional medium to attract consumer interest in Ucok Sticker products. This video is made using several software such as coreldraw, photohop and wondershare filmora x. It can be concluded that this research aims as a promotional advertisement and information to increase consumer attractiveness and sales. Researchers hope that this advertising video has better expectations for the future.